Discrete-time multiple resonant controller design for uninterruptible power supplies. Issue 1 (July 2017) - Keiel, Guilherme; Flores, Jeferson V.; Pereira, Luís F.A.; Salton, Aurelio T.
Abstract: This paper casts the design problem of multiple resonant controllers for uninterruptible power supplies in a robust discrete-time framework. Euler and Adams-Bashforth discretization methods are considered to describe the uncertain open-loop plant and periodic reference tracking/disturbance rejection is guaranteed by the introduction of a discrete-time resonant controller in the control loop. Controller parameters are determined by the solution of a convex optimization problem subject to linear matrix inequality constraints. Simulation results in 3.5kVA power inverter are considered to illustrate the method.